PENGARUH PENAMBAHAN KARAGENAN DAN SORBITOL PADA KUAT TARIK EDIBLE STRAW DARI NANAS SUBGRADE - Devi Urianty Miftahul Rohmah; Sri Windarwati; Wendianing Putri Luketsi (Universitas Darussalam Gontor, 2019)
Plastic waste is a globally important issue and needs to be addressed immediately. One of the plastic wastes that pollute the marine environment is plastic straws. One effort to reduce plastic straw waste is to make edible straws, eco-friendly straws or biodegradable straws. Pineapple is a fruit that is available throughout the season in Indonesia and its subgrade fruit production is only sold at a much cheaper price or even discarded. This study aims to utilize subgrade pineapple and analyze the effect of adding carrageenan and sorbitol on the tensile strength of edible straw from subgrade pineapple. This research uses the 2-factor Randomized Complete Design (CRD) method. The first factor is the concentration of carrageenan (K) consisting of 3 levels, 2% (w / w), 4% (w / w) and 6% (w / w). The second factor is the concentration of sorbitol (S) consisting of 3 levels, 8% (v / w), 10% (v / w) and 12% (v / w). The results showed that the addition of carrageenan and sorbitol influenced the tensile strength of edible straw from subgrade pineapple. Edible straw which has the highest average tensile strength is found in S1K3 (sorbitol 8% and carrageenan 6%).